If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (5y + 6) + -1(3y + 4y) = 10 Reorder the terms: (6 + 5y) + -1(3y + 4y) = 10 Remove parenthesis around (6 + 5y) 6 + 5y + -1(3y + 4y) = 10 Combine like terms: 3y + 4y = 7y 6 + 5y + -1(7y) = 10 Remove parenthesis around (7y) 6 + 5y + -1 * 7y = 10 Multiply -1 * 7 6 + 5y + -7y = 10 Combine like terms: 5y + -7y = -2y 6 + -2y = 10 Solving 6 + -2y = 10 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + -2y = 10 + -6 Combine like terms: 6 + -6 = 0 0 + -2y = 10 + -6 -2y = 10 + -6 Combine like terms: 10 + -6 = 4 -2y = 4 Divide each side by '-2'. y = -2 Simplifying y = -2
| a+4=-5a+5 | | 2.7x=0 | | -4b-5=10 | | z^3+3z^2+3z+1=0 | | -5(2y-6)-y=-3(y-3) | | n^2=3n+10 | | (x^9y)(x^9y)(x^9y)(x^9y)(x^9y)(x^9y)(x^9y)(x^9y)(x^9y)=0 | | 28x^8+16x^3-20x^6+12= | | 9x+11= | | 0.8x=-1.2y | | 90+0.60m=60+0.80m | | 4a+2=3b+5 | | 7x-2y=-2 | | 16w+14x=yforx | | -6x-5= | | m=-3.4 | | x^2-4x+4+49=0 | | -6x-9y=66 | | 9x-3x+6=x-9+15 | | 4(12g-6)=6(-4+5g)+18g | | 4X=x+10 | | z+3=4 | | log(15)1= | | (-2ab^2)(-2ab^2)(-2ab^2)=0 | | X^2=4x+24 | | 15-45=4(x-3)-6 | | 5(y+2)=6 | | 144x^2=25y^2 | | 16=6x | | x^2-3x-8=4 | | -2x^2-28x-98=-512 | | ln(-3x)=ln(x^2-54) |